2006
DOI: 10.1038/sj.bjc.6603507
|View full text |Cite
|
Sign up to set email alerts
|

The hollow fibre assay as a model for in vivo pharmacodynamics of fluoropyrimidines in colon cancer cells

Abstract: The Hollow Fibre Assay (HFA) is usually applied as an early in vivo model for anti-cancer drug screening, but is potentially an excellent model for short-term in vivo pharmacodynamic studies. We used the model to study the in vivo role of thymidine phosphorylase/ platelet-derived endothelial cell growth factor (TP/PD-ECGF) in the cytotoxicity and pharmacodynamics of TAS-102 in colon cancer cells. TAS-102 is a new oral drug formulation, which is composed of trifluorothymidine (TFT) and thymidine phosphorylase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
0
14
0
3
Order By: Relevance
“…15 Although these phenomena are known to be induced by microtubule inhibitors, such as taxanes, they are less expected to be associated with the activity of a nucleoside analog that targets the S-phase of the cell cycle, e.g., by TS inhibition and DNA damage induction. 24 The difference between TFT and 5-FU induced cell death was also found in in vivo experiments, in which TFT (as TAS-102) induced more tumor growth inhibition and caused more cell death than the 5-FU prodrug 5 0 -DFUR 37 . In other preclinical in vivo studies, TAS-102 also showed a better antitumor effect than various other 5-FU formulations, all at their MTD.…”
Section: Cancer Therapymentioning
confidence: 87%
See 2 more Smart Citations
“…15 Although these phenomena are known to be induced by microtubule inhibitors, such as taxanes, they are less expected to be associated with the activity of a nucleoside analog that targets the S-phase of the cell cycle, e.g., by TS inhibition and DNA damage induction. 24 The difference between TFT and 5-FU induced cell death was also found in in vivo experiments, in which TFT (as TAS-102) induced more tumor growth inhibition and caused more cell death than the 5-FU prodrug 5 0 -DFUR 37 . In other preclinical in vivo studies, TAS-102 also showed a better antitumor effect than various other 5-FU formulations, all at their MTD.…”
Section: Cancer Therapymentioning
confidence: 87%
“…Cells were retrieved and growth inhibition was determined by the MTT-assay and cell death by the TUNEL assay as described previously. 37 …”
Section: Hollow Fiber Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry was used to determine cell cycle distribution as well as the amount of apoptotic cells within the cell populations exposed to the drugs alone or in combination as described previously (Temmink et al, 2007). Cells at a density of 50 Â 10 3 cells per well were plated into flat bottom 6-well plates (Greiner Bio-One GmbH, Frickenhausen, Germany) and allowed to attach for 24 h prior to drug treatments at IC 50 concentrations.…”
Section: Cell Cycle and Apoptosis Analysismentioning
confidence: 99%
“…Along these lines, Hall and colleagues have used the hollow fiber assay to study the effects of cell cycle inhibitors on Rb expression and phosphorylation and PCNA expression 37. Temmink and colleagues used the model to study the in vivo role of thymidine phosphorylase/platelet-derived endothelial cell growth factor in the cytotoxicity and pharmacodynamics in colon cancer cells of a formulation of trifluorothymidine and a thymidine phosphorylase inhibitor 50. Sader et al have adapted the assay to study the molecular events involved as a human prostate cancer cell line (LNCaP) progresses to hormone independence 51.…”
Section: Additional Applications Of the Hollow Fiber Assaymentioning
confidence: 99%